Synthesis of highly dense MoO2/MoS2 core–shell nanoparticles via chemical vapor deposition. (11th November 2020) - Withanage, Sajeevi S; Charles, Vanessa; Chamlagain, Bhim; Wheeler, Robert; Mou, Shin; Khondaker, Saiful I
Abstract: Nanostructure morphologies of transition metal dichalcogenides (TMDs) are gaining much interest owing to their catalytic, sensing, and energy storage capabilities. Here, we report the synthesis of highly dense MoO2 /MoS2 core–shell nanoparticles, a new form of TMD nanostructure, via chemical vapor deposition using new growth geometry where a thin film of MoO3 was used as a source substrate for Mo as opposed to using MoO3 powder used in conventional studies. To grow the MoO2 /MoS2 core–shell nanoparticles, we precisely control the carrier gas flow rate and sulfur vapor introduction time with respect to the melting of a MoO3 thin film used for Mo precursor. Scanning electron microscope image shows dense coverage of nanoparticles of 50–120 nm in size. The transmission electron microscopy image shows that the nanoparticles consist of crystalline MoO2 core covered with a few layer MoS2 shell. Raman and energy dispersive spectroscopy characterizations further confirm the chemical composition of the nanoparticle containing MoO2 and MoS2 . We discuss the growth conditions under which the nanoparticles grow and elucidate its growth mechanism. We also discuss how a small but controllable changes in growth condition could lead to other highly dense growth of vertical/lateral MoO2 /MoS2 plates in both source and growth substrates due to the unique growth geometry used in this study.